IMPLEMENTASI KEBIJAKAN PELAYANAN KESEHATAN IBU DAN ANAK DI KABUPATEN TAKALAR PROVINSI SULAWESI SELATAN - tiah, Halwa (Universitas 17 Agustus 1945 Surabaya, 2016)
Takalar district, South Sulawesi has a policy of maternal and child healthby adopting indigenous shaman a major role in the birthing process in theform of Regulation No. 2 of 2010 on the Partnership midwife and healer.Based on the subject matter, the question of the proposed research is howthe implementation of policies on Maternal and Child Health in Takalardistrict, South Sulawesi? How to model Policy Implementation Maternaland Child Health Care according to local conditions in the district of SouthSulawesi Takalar? The method used is descriptive qualitative. The resultsshowed that the results are good policy performance. The success of thepolicy program at the district MCH-KBD Takalar this policy to be a